2005
DOI: 10.1111/j.1474-9726.2005.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in regional brain mitochondria from Fischer 344 rats

Abstract: SummaryBrain mitochondrial function has been posited to decline with aging. In order to test this hypothesis, cortical and striatal mitochondria were isolated from Fischer 344 rats at 2, 5, 11, 24 and 33 months of age. Mitochondrial membrane potential remained stable through 24 months, declining slightly in mitochondria from both brain regions at 33 months. The ability of calcium to induce mitochondrial swelling and depolarization, characteristics of the permeability transition, was remarkably stable through 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Recently, we showed that naïve F344 rats display no age-related deficits in mitochondrial respiration (Gilmer et al, 2010), therefore deficits may not be apparent until the mitochondria are challenged. Other data support these findings in F344 rats, including those that show that mitochondrial membrane potential and susceptibility to permeability transition was stable out to 24 months (LaFrance et al, 2005).…”
Section: Discussionmentioning
confidence: 58%
“…Recently, we showed that naïve F344 rats display no age-related deficits in mitochondrial respiration (Gilmer et al, 2010), therefore deficits may not be apparent until the mitochondria are challenged. Other data support these findings in F344 rats, including those that show that mitochondrial membrane potential and susceptibility to permeability transition was stable out to 24 months (LaFrance et al, 2005).…”
Section: Discussionmentioning
confidence: 58%
“…The drop mΔΨ in brain mitochondria of WKY and SHR rats due to the addition of Ca 2+ excess (160, 480, and 640 nmol Ca 2+ ) was restored by the addition of Ca 2+ chelating agents, this suggest that Ca 2+ excess did not cause mitochondrial damage, which would be attributed to the relative resistance of brain mitochondria to Ca 2+ overload. Accordingly, other studies found that depending on the brain region, mitochondria are differentially sensitive to Ca 2+ overload (LaFrance et al, 2005;Brown et al, 2006), without undergoing mitochondrial permeability transition (Berman et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…Liver mitochondria from old rats showed decreased membrane potential, an impairment that was improved by treatment with an antioxidant extract (139). Cortical and striatal mitochondria of aged rats showed lower membrane potentials with increased susceptibility to the permeability transition at advanced ages (88). Mitochondria isolated from thoraces of Drosophila melanogaster, mainly flight muscle mitochondria, showed a significant decrease in state 3 respiration, respiratory control ratios, and uncoupled respiration rates, as a function of age, using either NAD-or FAD-linked substrates, but there were no differences in state 4 respiration rates, which does not indicate increased H ϩ permeability in aging (51).…”
Section: Increased H ϩ Permeability Of the Inner Membranementioning
confidence: 99%